Assessing the impact of law enforcement to reduce over-the-counter (OTC) sales of antibiotics in low- and middle-income countries; a systematic literature review - Tom G. Jacobs; Jane Robertson; Hendrika A. van den Ham; Kotoji Iwamoto; Hanne Bak Pedersen; Aukje K. Mantel-Teeuwisse (BMC, 2019)
Abstract Background Many low- and middle-income countries (LMIC) are moving towards enforcing prescription-only access to antibiotics. This systematic literature review aims to assess the interventions used to enforce existing legislation prohibiting over-the-counter (OTC) sales of antibiotics in LMICs, their impact and examine the methods chosen for impact measurement including their strengths and weaknesses. Methods Both PubMed and Embase were systematically searched for studies reporting on impact measurement in moving towards prescription only access to antibiotics in LMICs. The PRISMA methodological review framework was used to ensure systematic data collection and analysis of literature. Narrative data synthesis was used due to heterogeneity of study designs. Results In total, 15 studies were included that assessed policy impact in 10 different countries. Strategies employed to enforce regulations prohibiting OTC sales of systemic antibiotics included retention of prescriptions for antibiotics by pharmacies, government inspections, engaging pharmacists in the design of interventions, media campaigns for the general public and educational activities for health care workers. A variety of outcomes was used to assess the policy impact; changes in antimicrobial resistance rates, changes in levels of antibiotic use, changes in trends of antibiotic use, changes in OTC supply of antibiotics, and changes in reported practices and knowledge of pharmacists, medicine sellers and the general public. Differences in methodological approaches and outcome assessment made it difficult to compare the effectiveness of law enforcement activities. Most effective appeared to be multifaceted approaches that involved all stakeholders. Monitoring of the impact on total sales of antibiotics by means of an interrupted time series (ITS) analysis and analysis of pharmacies selling antibiotics OTC using mystery clients were the methodologically strongest designs used. Conclusions The published literature describing activities to enforce prescription-only access to antibiotics in LMICs is sparse and offers limited guidance. Most likely to be effective are comprehensive multifaceted interventions targeting all stakeholders with regular reinforcement of messages. Policy evaluation should be planned as part of implementation to assess the impact and effectiveness of intervention strategies and to identify targets for further activities. Robust study designs such as ITS analyses and mystery client surveys should be used to monitor policy impact.